ANALISIS DEBIT BANJIR DRAINASE JALAN PATTIMURA KOTA TARAKAN DAN PENGARUHNYA TERHADAP KAPASITAS SALURAN - Ruslan, Ruslan; Amiruddin, Aswar; Faizal, Rahmat (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2024)
ABSTRACT: Tarakan City has a large problem of land conversion which results in a decrease in the infiltration area. Jalan Pattimura, Pamusian Kelurahan is one of the points in Central Tarakan District that has the potential for flooding due to high rainfall intensity. The purpose of this study is to calculate the flood discharge Q25, Q50 and Q100 and to evaluate the channel capacity against the flood discharge. The method used to calculate the discharge is the modified rational method. The design flood discharge with a return period of 25, 50 and 100 years in the catchment area of drainage channel 1 is calculated using the modified rational method is 0,112 m3/sec for Q25, 0,115 m3/sec for Q50 and 0,117 m3/sec for Q100. Furthermore, the design flood discharge in the catchment area of drainage channel 2 is calculated using the modified rational method is 0,111 m3/sec for Q25, 0,113 m3/sec for Q50 and 0,115 m3/sec for Q100. Based on the evaluation of the existing channel conditions of Jalan Pattimura, Pamusian Kelurahan, Tarakan City, it was obtained that the existing channel capacity with the existing channel height is able to pass a discharge of 0,366 m3/sec for Drainage Channel 1 and 0,312 m3/sec for Drainage Channel 2 so it can be concluded that the current channel is still able to pass the discharge Q25, Q50 and Q100 years. Keywords: Drainage, flood discharge, channel capacity ABSTRAK: Kota Tarakan memiliki masalah alih fungsi lahan yang besar yang berakibat pada berkurangnya daerah resapan. Jalan Pattimura, Kelurahan Pamusian merupakan salah titik di Kecamatan Tarakan Tengah yang memiliki potensi banjir akibat intensitas hujan yang tinggi. Tujuan penelitian ini untuk menghitung debit banjir Q25, Q50 dan Q100 dan melakukan evaluasi kapasitas saluran terhadap debit banjir. Metode yang digunakan untuk menghitung debit adalah rasional modifikasi. Debit banjir rencana periode ulang 25, 50 dan 100 tahun pada daerah tangkapan saluran drainase 1 dihitung menggunakan metode rasional modifikasi adalah 0,112 m3/dtk untuk Q25, 0,115 m3/dtk untuk Q50 dan 0,117 m3/dtk untuk Q100. Selanjutnya, debit banjir rencana pada daerah tangkapan saluran drainase 2 dihitung menggunakan metode rasional modifikasi rasional adalah 0,111 m3/dtk untuk Q25, 0,113 m3/dtk untuk Q50 dan 0,115 m3/dtk untuk Q100. Berdasarkan evaluasi terhadap kondisi saluran eksisting Jalan Pattimura, Kelurahan Pamusian, Kota Tarakan diperoleh kapasitas saluran eksisting dengan tinggi saluran yang ada saat mampu melewatkan debit 0,366 m3/dtk untuk Saluran Drainase 1 dan 0,312 m3/dtk untuk Saluran Drainase 2 sehingga dapat disimpulkan saluran yang saat ini masih mampu melewatkan debit Q25, Q50 dan Q100 tahun.Kata kunci: Drainase, debit banjir, kapasitas saluran